(untitled) (REMUNOM, 2024)
It is undeniable that smile aesthetics has been increasingly valued. Depending on what an individual considers a beautiful smile and what it represents in his or her life, the dissatisfaction with one or more characteristics of the smile leads to problems of self-esteem and self-image, which, in turn, motivates the individual to seek aesthetic dentistry in order to feel more beautiful, confident and accepted. This study was cross-sectional, observational, with an inductive approach and comparative and descriptive procedure, in which a specific questionnaire was adopted as a data collection strategy. The present study aimed to evaluate the self-perception of the smile of dentistry students at the Federal University of Campina Grande, Patos campus, Paraíba. The research project was sent to the Human Research Ethics Committee of the Centro Universitário de Patos, and approved under opinion number 4.817.342. This study aimed to evaluate the self-perception of the smile of undergraduate dental students at the Federal University of Campina Grande, Patos Campus, Paraíba. Data collection was performed through a questionnaire directed at undergraduates from the 1st to the 10th period of the Dentistry Course, encompassing questions about the self-perception of smile aesthetics. It was found that 64% of the participants are satisfied with their smile and that 51.6% are confident and secure in relation to it, but that despite this, 89.4% would like to change something and 88.5% would perform some aesthetic dental treatment, being the color (66.6%), position (42.5%) and shape (30.3%) of the teeth respectively the most desired changes. Thus, it was possible to conclude that the participants, although satisfied with their smiles, reported wanting to make some changes in their teeth, which shows a certain concern with their appearance.